Perú Promesa (Peru Promise): presentation speech - Pacheco Vélez, César (1988)
​The following is the last public speech given by Dr. César Pacheco Vélez (1929-1989),  on the occasion of the presentation of the book "Perú Promesa". The Editorial Board of Apuntes wants thus to give a posthumous homage to that outstanding historian and friend.